Electromechanical modeling of human ventricles with ischemic cardiomyopathy: numerical simulations in sinus rhythm and under arrhythmia. (September 2021) - Salvador, Matteo; Fedele, Marco; Africa, Pasquale Claudio; Sung, Eric; Dede', Luca; Prakosa, Adityo; Chrispin, Jonathan; Trayanova, Natalia; Quarteroni, Alfio
Abstract: We developed a novel patient-specific computational model for the numerical simulation of ventricular electromechanics in patients with ischemic cardiomyopathy (ICM). This model reproduces the activity both in sinus rhythm (SR) and in ventricular tachycardia (VT). The presence of scars, grey zones and non-remodeled regions of the myocardium is accounted for by the introduction of a spatially heterogeneous coefficient in the 3D electromechanics model. This 3D electromechanics model is firstly coupled with a 2-element Windkessel afterload model to fit the pressure-volume (PV) loop of a patient-specific left ventricle (LV) with ICM in SR. Then, we employ the coupling with a 0D closed-loop circulation model to analyze a VT circuit over multiple heartbeats on the same LV. We highlight similarities and differences on the solutions obtained by the electrophysiology model and those of the electromechanics model, while considering different scenarios for the circulatory system. We observe that very different parametrizations of the circulation model induce the same hemodynamical considerations for the patient at hand. Specifically, we classify this VT as unstable. We conclude by stressing the importance of combining electrophysiological, mechanical and hemodynamical models to provide relevant clinical indicators in how arrhythmias evolve and can potentially lead to sudden cardiac death. Highlights: We present an individualized computational model of electromechanical activity in the left ventricle of a patient with ischemic cardiomyopathy (ICM). The mathematical parametrization keeps into account the contribution of scar, grey zone and non-remodeled regions in the myocardium. We calibrate the pressure-volume loop of the ICM patient-specific human left ventricle in sinus rhythm. We perform numerical simulations of the electromechanical activity under ventricular tachycardia (VT). Our approach is able to identify hemodynamically unstable VTs.